Bacteriophages: a double-edged sword in the gastrointestinal tract - Wei, Yuqi (Frontiers in Microbiomes, 2024)
The symbiotic relationship between the gut microbiome and the human body is a concept that has grown in popularity in recent years. Bacteriophages (phages) are components of the gut microbiota and their imbalance plays a role in the pathogenesis of numerous intestinal disorders. Meanwhile, as a new antimicrobial agent, phage therapy (PT) offers unique advantages when compared with antibiotics and brings a new dawn for treatment of multidrug-resistant bacteria in intestinal and extraintestinal disorders. In this review, we provide a brief introduction to the characterization of phages, particularly focusing on newly discovered phages. Additionally, we outline the involvement of gut phages in disease pathogenesis and discuss the status and challenges of utilizing phages as therapeutic targets for treatment of enteric infection.